ANALISIS REGRESI LINEAR BERGANDA DENGAN SATU VARIABEL BONEKA (DUMMY VARIABLE) - Tanti Krisnawardhani; Nur Salam; Dewi Anggraini (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2010)
To accommodate the existence of free qualitative variables into the regression model then used variable dummy (variable dummy) in the regression equation that can be written as follows: i i i i Y     X   D  0 1 2. This study aims to determine parameter estimation of the multiple linear regression model with one variable the puppet uses the least squares method, determining the model match test statistic using the method likelihood ratio and apply the model in the case example. The results showed that the parameter estimation of the regression model is: β  X'X (X'Y) 1  . Application of usage this regression model is in the example about the calculation of tuition fees Y based on the average Scholastic Aptitude Test (X nilai) and university type D so obtained the following model: Y  7263,56 19,52X  8732,418D 